Advanced classification techniques for healthcare analysis - Chakraborty, Chinmay 1984- (A volume in the Advances in medical technologies and clinical practice (AMTCP) book series, 2019)
"This book focuses on classification techniques which broadly deals in delivery of quality, accurate and affordable healthcare. It also examines the potential for making faster advances in many scientific disciplines and improving the profitability and success of different enterprises"...Provided by publisher